2019
DOI: 10.1002/batt.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Designed CNF/S−Cu/CNF Nonwoven Electrode as Free‐Standing Cathode for Lithium−Sulfur Batteries

Abstract: A flexible lithiumÀsulfur (LiÀS) battery cathode is prepared through uniformly depositing sulfur solution into an electrospun N-rich and Cu-decorated nonwoven carbon nanofiber (CNF) film to form sandwich structured CNF/SÀCu/CNF film electrodes. As a free-standing cathode of LiÀS battery, the unique structural CNF/SÀCu/CNF composite cathodes exhibit high capacity and rate capability as well as long cycling stability. The electrodes can deliver a reversible capacity of 1295 mAh g À1 at a current density of 0.1 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…CNT paper-based current collectors have been used to support various active materials, such as V 2 O 5 , 245 LiFePO 4 , 246 Li 4 Ti 5 O 12 , 247 and NCM. 248 The recent arise of interests in high-energy Li-S batteries have triggered tremendous efforts to the development of sulfur cathodes, 249,250 electrolytes, 45 and lithium metal anodes. 251 Peng et al 241 demonstrated a flexible CNT-based sulfur electrodes to increase sulfur contents, curtail passivation layers, as well as promote redox kinetics of sulfur interconversions ( Figure 13B).…”
Section: Planar Structuresmentioning
confidence: 99%
“…CNT paper-based current collectors have been used to support various active materials, such as V 2 O 5 , 245 LiFePO 4 , 246 Li 4 Ti 5 O 12 , 247 and NCM. 248 The recent arise of interests in high-energy Li-S batteries have triggered tremendous efforts to the development of sulfur cathodes, 249,250 electrolytes, 45 and lithium metal anodes. 251 Peng et al 241 demonstrated a flexible CNT-based sulfur electrodes to increase sulfur contents, curtail passivation layers, as well as promote redox kinetics of sulfur interconversions ( Figure 13B).…”
Section: Planar Structuresmentioning
confidence: 99%
“…To this end, it is important to seek a suitable approach to efficiently enhance the chemical interactions between the carbon hosts and LiPSs. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…To this end, it is important to seek a suitable approach to efficiently enhance the chemical interactions between the carbon hosts and LiPSs. 22,23 Heteroatoms doping (e.g., N, P, S, O, and B et al) was proposed as an effective strategy to enhance the polarity of carbon hosts and improve their adhesion toward LiPSs. 24−27 The addition of extra metal-based materials including metal, 28−30 metal oxides, 31−34 metal carbides, 35−37 metal sulfides, 38−41 metal nitrides, 42−45 and transition metal phosphides (TMPs) 46−48 to the doped carbon has recently been found to be extremely effective in further enhancement of the chemical affinity between carbon hosts and LiPSs, and thus mitigate the shuttling effect.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] However, there are still multiple obstacles leading to poor cycle stability and rate performance, which inhibits the commercialization of LiÀ S battery. [7,8] They are mainly reflected in the following aspects: i) the inherent insulation of sulfur cathode and its reduction products Li 2 S/Li 2 S 2 , which induces low electron transport rate and the utilization of the sulfur species. ii) The shuttle effect of soluble LiPS intermediates in the electrolyte, leading to poor Coulombic efficiency.…”
Section: Introductionmentioning
confidence: 99%